2014
DOI: 10.1111/eje.12124
|View full text |Cite
|
Sign up to set email alerts
|

Virtual classroom helps medical education for both Chinese and foreign students

Abstract: Our results suggest that computerised teaching methods have significant potential to assist in learning for both Chinese and foreign medical undergraduates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The role of virtual classrooms in student's achievement, 28 (56.0%) students thought VC lead to high academic achievement rate. This finding agrees with Shi et al's (2014) study indicated that the computed teaching method as in virtual classrooms have great potential to provide assistance in learning for all medical undergraduate students. Cook's (2012) study revealed that the audio-visuals aids have a vital role in teaching and learning of medical students.…”
Section: Seven Technologiesupporting
confidence: 91%
“…The role of virtual classrooms in student's achievement, 28 (56.0%) students thought VC lead to high academic achievement rate. This finding agrees with Shi et al's (2014) study indicated that the computed teaching method as in virtual classrooms have great potential to provide assistance in learning for all medical undergraduate students. Cook's (2012) study revealed that the audio-visuals aids have a vital role in teaching and learning of medical students.…”
Section: Seven Technologiesupporting
confidence: 91%
“…A large portion said the use of computerized methods in teaching is a useful addition to the studies where it can be concluded that computerized teaching methods have the potential to help dentistry undergraduate students [13]. Although our study did not evaluate the importance of digital methods in oral medicine teaching, we can affirm that the virtual platform provides a great material and a supplement for students as an adequate form of study.…”
Section: Discussionmentioning
confidence: 64%
“…The association between regular classes and with a virtual learning environment through Moodle has demonstrated the feasibility to improvements in student performance in stomatology being able to overextend to foreign students of isolated regions where the technology is under development [13].…”
Section: Discussionmentioning
confidence: 99%
“…24 Usage of virtual classrooms supported better educational outcomes among Chinese and foreign students in China in three medical schools. 25 Such outcome is associated with great relevant importance considering the need for distant education implementation due to the COVID-19 pandemic conditions.…”
Section: Resultsmentioning
confidence: 99%